Imperata yellow mottle virus: An Emerging Threat to Maize, Sorghum and Pearl Millet in Burkina Faso - Koala, Moustapha; Traoré, Valentin Stanislas Edgar; Sérémé, Drissa; Neya, Bouma James; Brugidou, Christophe; Barro, Nicolas; Traoré, Oumar (Scientific Research, 2017)
Imperata yellow mottle caused by Imperata yellow mottle virus (IYMV) of the genus Sobemovirus was first characterized on Imperata cylindrica and Zea mays in Burkina Faso. The disease has been reported in several localities of the country but its ecology and epidemiology are poorly known. In particular, only I. cylindrica and maize have been reported within IYMV host range. The aim of this study was to investigate the experimental host range of the virus. Mechanical inoculation of a mixture of four IYMV isolates to 18 plant species, including four crops (maize, rice, sorghum and pearl millet) and 14 wild grasses showed clear mottle symptoms in maize, sorghum and pearl millet and two wild grass species (Setaria verticillata and Rottboellia exaltata). Symptom development was confirmed by Enzyme-linked immunosorbent assay and reverse transcription–polymerase chain reaction (RT-PCR). Infection of crop species by IYMV depended on cultivars tested. Therefore, proportions of positive cultivars were 16/36 in maize, 4/10 in sorghum and 4/9 in pearl millet, respectively. Studies on virus-host interactions using individual virus isolates showed two pathogenic patterns. Three out of the four isolates tested infected all plant species and cultivars. In contrast, the fourth IYMV isolate could infect only one maize cultivar. These results expand the previously known host range of IYMV from two to five species, indicating a narrow host range. Among the new characterized host species, sorghum and pearl millet are important cereal crops. Therefore, Imperata yellow motte disease is a potential threat for the cereal crop production and its ecology and epidemiology should be thoroughly investigated.
Keywords: IYMV; Sobemovirus; Host Range; Virus-Host Interactions